2016
DOI: 10.1103/physreve.93.042135
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of correlations in interacting systems

Abstract: A fundamental connection between thermodynamics and information theory arises from the fact that correlations exhibit an inherent work value. For noninteracting systems this translates to a work cost for establishing correlations. Here we investigate the relationship between work and correlations in the presence of interactions that cannot be controlled or removed. For such naturally coupled systems, which are correlated even in thermal equilibrium, we determine general strategies that can reduce the work cost… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Interestingly, it allows for better cooling than the case where no correlations are present. This is in agreement with recent work that has shown that correlations can play a role in work extraction and entropy flows in cooling protocols [22][23][24][25][26][27][28][29].…”
Section: Introductionsupporting
confidence: 93%
“…Interestingly, it allows for better cooling than the case where no correlations are present. This is in agreement with recent work that has shown that correlations can play a role in work extraction and entropy flows in cooling protocols [22][23][24][25][26][27][28][29].…”
Section: Introductionsupporting
confidence: 93%
“…(10) This results in the impossibility to extract energy from locally thermal states of non interacting systems, while this is possible for interacting systems. This has motivated the study of the energetics of correlations in interacting systems [45].…”
Section: Results For Locally Thermal Statesmentioning
confidence: 99%
“…To formulate our ideas we adopt a commonplace view in quantum thermodynamics, namely, that work is a central resource that is required to move systems away from freely available thermal equilibrium states [24]-an approach that has staged a diverse range of investigations within the broader field [25][26][27]. In this paradigm, previous research has investigated the work-cost (or gain) of quantum processes [28][29][30][31][32], refrigeration [33,34], or for establishing correlations [35][36][37][38].…”
Section: Tpm Schemementioning
confidence: 99%